Eribulin in non-small cell lung cancer: challenges and potential strategies. (3rd April 2017) - Swami, Umang; Shah, Umang; Goel, Sanjay
ABSTRACT: Introduction : Eribulin is a non-taxane, macrocyclic, synthetic, ketone analog of halichondrin B with a microtubule inhibitory action specific toward plus ends. It is approved by United States Food and Drug Administration (USFDA) for the treatment of patients with unresectable or metastatic liposarcoma who have received a prior anthracycline-containing regimen. It is also approved as a third line therapy for patients with metastatic breast cancer who have received a prior treatment with anthracycline and taxane in either adjuvant or metastatic setting. It has also undergone investigation in various cancers including non-small cell lung cancer (NSCLC). Areas covered : This review covers eribulin in detail with regards to pharmacodynamics, mechanism of action, pharmacokinetics, published phase I studies along with special focus on phase II and III studies of eribulin in NSCLC. Expert opinion : Eribulin is a potent chemotherapeutic agent with acceptable and easily manageable toxicity profile. It has shown activity in NSCLC. However, the management of NSCLC is undergoing rapid evolution with introduction of newer immune mediated and targeted agents. The way to move forward is to combine eribulin with novel immune checkpoint inhibitors, targeted agents and chemotherapies in appropriate line of therapy.